The scientific and practical way to choose scientific research topic and give it a title - Rebbahi, Mostafa; Khelifi, Chawki (Journal of Human Sciences, 2022)
The most difficulty, which any researcher facing with, in the scientific field, mainly for  master and doctoral student , is the choice of a scientific research topic, especially since they are restricted by a specified time, for this, and to passing  this delicate phase, the researcher must follows a specific steps in accordance with scientific and practical methodology that includes a set of conditions and norms that must be respected in this regard,  which we are addressing in first time.But, the choice of a theme will remain  meaningless, unless we put it in a framework  that defines it, we mean here, to give any  subject research its scientific meaning, it must make it a meaningful title that constitutes its scientific identification card, as succeeding  to formulate some title means the success in the choice of  scientific research topic, and consequently success in achieving the objectives that are desired by this research, the question that can only be achieved by respecting a set of the criteria  and conditions when formulating the title which we are addressing  in second time .